Utilization Management of Landfill Zones Based on Volume of Municipal Organic Waste Simulation - Philip Faster Eka Adipraja; Mufidatul Islamiyah; Ida Wahyuni (IPTEK The Journal for Technology and Science, 2018)
Talangagung landfill is one of the zones that well managed by the government of Malang Regency which uses sanitary landfill method. Additionally, it’s also succeeded in the utilization of methane gas which has already distributed to the residents around the landfill directly from the landfill zones for daily purposes. For a couple of years, the processing of municipal waste in Talangagung is quite well, however, the significant increase in the waste generation could lead to new management problems in the landfill. The prediction on the waste volume on next 20 years shows that the increased amount of waste volume soon or later will exceed the current capacity of landfill zones. The previous study about waste degradation shows the different time periods of degradation in various waste as fast as just about a month to more than 7 months. The simulation from this study shows that around 2004 require 2 landfill zones to use simultaneously. Hereafter, the prediction shows while in 2018 the landfill requires 3 zones used simultaneously, starts from 2025 there is necessary to use 4 zones simultaneously. Based on the simulation result, the landfill will overload in around 2026. The models in this study were validated with a small error of E1 about 2.33% and the error of E2 about 0.76%.